Analysis of the current situation of college students’ achievement motivation and influencing factors—an empirical analysis based on a college in Shandong Province - Dang, Shiying; Jin, Yan; Niu, Xingmeng; Wang, Junyu; Yu, Wenpei; Zhou, Weijun; Sun, Hao; Xie, Hui (Frontiers in Psychology, 2025)
BackgroundCollege students’ academic success and future growth are greatly impacted by achievement motivation, an innate desire for excellence. Higher education is an important time for students to socialize, and achievement motivation has a big impact on personal values, which is important for producing top-notch workers.ObjectiveThe purpose of this study was to examine the current state of college students’ achievement motivation and the elements that influence it.Methods2,849 students from a university in Shandong Province participated in a cross-sectional survey. The Achievement Motivation Scale was used to measure the motivation to strive for achievement vs. the motivation to avoid failure. SPSS version 27.0 was utilized for conducting descriptive statistics, single-factor analysis, and performing multiple linear regression analysis.ResultsCollege students’ average achievement motivation score was 4.38 ± 12.99, with a noticeably unequal distribution across motivation levels. Gender, parental literacy level, personal and parental health condition, family annual income, future goals, and short-term plans all showed statistically significant variations in achievement motivation, according to a single-factor analysis (p < 0.05). However, multiple linear regression analysis showed that the direct effects of variables like family annual income and parental literacy level were no longer significant after adjusting for inter-variable interactions.ConclusionThis study confirms that gender, personal health condition, and short-term plans are important influencing factors and demonstrates considerable individual differences in university students’ achievement motivation with an uneven overall distribution. It offers both practical advice and theoretical foundations for applying differentiated instruction in higher education settings.